Esiste davvero la Biblioterapia? Analisi della disciplina e possibili applicazioni nelle biblioteche - Dalla Valle, Marco (2017)
Bibliotherapy is the innovative way to creatively use literature to improve people’s wellness. The library is a quiet place where Bibliotherapy projects may be developed, as libraries are able to allow the readers in a silent place. In this article we describe three bibliotherapy activities in libraries: book on prescription, development (or creative) bibliotherapy in groups, interaction between library services and health services. These are examples of integration between social services for rehabilitation of psichiatric people and library services. In addition, libraries can become a place where search for information about our illness. In our State similar experiences have never been described. It is possible to postulate the ways to realize similar projects in Italy as well.
Keywords: biblioterapia; psichiatria; biblioteca; libri; benessere; libraries Italy; bibliotherapy practice; bibliotherapy Italy; bibliotherapy